Anaesthetic Management of Renal Transplant Surgery in Patients of Dilated Cardiomyopathy with Ejection Fraction Less Than 40% - Divya Srivastava; Tanmay Tiwari; Sandeep Sahu; Abhilash Chandra; Sanjay Dhiraaj (Anesthesiology Research and Practice)
Cardiovascular disease (CVD) is an important comorbidity of chronic kidney disease, and reducing cardiovascular events in this population is an important goal for the clinicians who care for chronic kidney disease patients. The high risk for CVD in transplant recipients is in part explained by the high prevalence of conventional CVD risk factors (e.g., diabetes, hypertension, and dyslipidemia) in this patient population. Current transplant success allows recipients with previous contraindications to transplant to have access to this procedure with more frequency and safety. Herein we provide a series of eight patients with dilated cardiomyopathy with poor ejection fraction posted for live donor renal transplantation which was successfully performed under regional anesthesia with sedation.